Ionic organic terahertz crystals: a perspective on design and solid-state phonon absorption - Kwon, O. Pil; Jazbinsek, Mojca (Journal of Materials Chemistry C, 2024)
Ionic organic nonlinear optical crystals have been established as efficient terahertz (THz) wave generators with a high generated THz power and a very wide bandwidth and can also be used as ultra-broad THz detectors. In this perspective, we discuss various design strategies to obtain high-performance ionic organic THz crystals. The introduction of aromatic coulombic interaction groups and acentric head-to-tail cation-anion assembly groups, as well as the control of the van der Waals volume of aromatic ions, are common to many top-level ionic organic THz crystals. Solid-state molecular and phonon vibrations of these crystals strongly influence the characteristics of THz generation and detection, in addition to their optical and nonlinear optical properties. The THz vibrational modes depend on the chemical structure, intermolecular interaction ability, crystal structure, void volume, and crystal density of organic THz crystals. To give a perspective on the future design of optimized ionic organic THz crystals and the influence of their phonon modes on ultra-broadband THz applications, we discuss both the structural factors that influence these modes and their specific influence on THz optical properties.
Keywords: Ionic organics; Optical-; Organic nonlinear optical crystals; Phonon absorption; Power; Solid state phonons; Tera Hertz; Terahertz detectors; Wave generators; Wide bandwidth